Association between serum 25-hydroxyvitamin D and carotid atherosclerotic plaque in Chinese type 2 diabetic patients. Issue 13 (March 2017) - Ding, Ya-Hui; Wei, Tie-Ming; Qian, Lin-Yan; Ma, Yuan; Lao, Di-Bo; Yao, Bin; Pang, Jie
Abstract : Abstract: In this study, we investigated the distribution of vitamin D and its association with carotid atherosclerotic plaque (CP) in Chinese type 2 diabetic (T2D) patients. We performed a cross-sectional study in 210 T2D and 94 age- and gender-matched nondiabetic patients during winter months, by determining serum 25-hydroxyvitamin D (25(OH)D) levels in both diabetic and nondiabetic controls. We carried out measurements of B-mode ultrasonography of carotid arteries in each T2D patient. The 25(OH)D concentration was 26.25 nmol/L among the T2D patients. About 93.3% T2D patients suffered from hypovitaminosis D. First, we found a clear inverse correlation between the 25(OH)D concentration and CP ( P  <0.001). Second, an association between 25(OH)D and macrovascular disease was significant ( P  = 0.005). In multivariate logistic regression analysis, decreasing 25(OH)D concentration was markedly associated with CP in T2D patients. Third, after adjusting for the confounding factors, we also observed a positive correlation between low levels of 25(OH)D in T2D patients with CP, when the following parameters were measured: old age (odds ratio [OR] = 2.533, P  = 0.013); smoking (OR = 3.872, P  = 0.001); and high level of low-density lipoprotein (LDL) cholesterol (OR = 2.776, P  = 0.009). Thus, we concluded that high prevalence of hypovitaminosis D exists in Chinese T2D patients. Further, we found a significant association between low concentration of serum 25(OH)D and the existence of high body mass index, and high circulating LDL to be substantially positive predictors of patients with CP in T2D.